(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article discusses the social and economic challenges faced by Central Asian countries in the early years of their independence, the reforms implemented by governments to address these issues, the regulation of relations between the state and religion, and the creation of legal frameworks to ensure citizens’ freedom of conscience. The significance of these laws and measures is also highlighted.